Firm size distortions under duopoly - González-Maestre, Miguel; Peñarrubia, Diego (Estudios de Economía, 2017)
Motivated by the fact that some regulations involve extra costs for those firms at a size beyond a critical threshold, this paper contributes to the analysis of the welfare distortions due to these regulations. In the context of a duopoly, our results show that social welfare is not monotonic with the regulatory threshold. In particular, we obtain the paradoxical result that a policy decision of increasing the threshold might involve a dramatic decrease in welfare in some markets. An interesting consequence of this result is that the positive discrimination towards small firms is a rather subtle issue. Our results suggest that the relevant regulatory thresholds should differ across industries. Apparently, this is taken into account in some countries (e.g., USA), but not in many other countries.